Current role of optical coherence tomography angiography: Expert panel discussion - Aniruddha Agarwal; Dilraj S Grewal; Glenn J Jaffe; Michael W Stewart; Sunil Srivastava; Vishali Gupta (Indian Journal of Ophthalmology, 2018)
Optical coherence tomography (OCT) angiography is a promising technique that provides depth resolved images of blood flow in the retina and choroid with levels of detail far exceeding that obtained with older forms of imaging and offers several advantages over conventional angiography to visualize the chorioretinal vasculature in a rapid and noninvasive manner. However, as with any evolving imaging technique, there are ongoing challenges in terms of need for new equipment, limitations of imaging capability and software processing techniques, as well as in understanding the implications of the imaging and its correlation with pathophysiology of the retina and choroid. This expert panel discussion is structured to provide an insight into the current state of OCT angiography.